Visualization of Covid 19 Information in Banten Province Based on Android - Yusuf Al Khairi; Ahmad Zuhdi; Ratna Shofiati (Penerbitan Universitas Trisakti, 2022)
Information visualization is a method for delivering information in visual form. Information visualize is vital if information about covid 19 is presented to the public, especially in the Province of Banten. Because the covid-19 virus is still high in the Province of Banten, as well as the lack of information about the spread of the covid-19 virus, there is need for caution so that the number of cases can be suppressed and may not increase. This requires A Covid 19 Information Visualize Android Application To Educate People In The Province Of Banten. So people can find out information about the covid-19 virus case. The application uses waterfall methodology for analysis that will identify the problem, data collection for android based information visualization. The next step is the design to design an android interface system app. Squence diagram, use case, erd (entity relationship diagram), and activity diagram are used for system design diagram. Based on the research from the android based app that will show information's visualization of covid 19.